Estudio de factibilidad de un método de microextracción en medio micelar (CPE) asistido por nanopartículas de plata para la determinación de cadmio mediante espectrometría de absorción atómica con calentamiento electrotérmico (ETAAS) (2020)
In this study, the development of a preconcentration method based on the CPE technique will be proposed, making use of Triton X-114 as an extractant micellar phase for the quantification of cadmium at levels of micrograms per liter (æg / L, ppb) in various aqueous matrices. For this, the cloud point extraction conditions must be optimized, as well as the establishment of the instrumental parameters for the determination of cadmium by means of electrothermal atomic absorption spectroscopy (ETAAS).